Personal Branding Brigadir Agus Kurniawan untuk Meningkatkan Citra Polisi Melalui Aplikasi Tiktok - Fitriyani, Ririn Desi; Rusdiana, Joni (UIN Raden Mas Said Surakarta, 2023)
In recent years, the image of the police has declined with various cases involving the names of POLRI members, this will of course have an impact on the level of public trust in the POLRI itself. However, this is in contrast to what Brigadier Agus Kurniawan, a Bhabinkamtibnas officer in Jeron Village, Boyolali Regency, did. He provides creative services and is named Kopi Curhat Pak Bhabin which is uploaded via the tiktok account @kopi_curhat_pakbhabin. This research aims to find out what kind of personal branding you want to show to the public. The research method used is descriptive qualitative with personal branding theory. With the conclusion that the personal branding shown is in accordance with Rampersad & Montoya’s 11 personal branding criteria, namely; Authenticity, Integrity, Consistency, Specialization, Authority, Distintiveness, Relevant, Visibility, Persistence, Goodwill, and Performance. The personal branding efforts carried out by Brigadier Agus Kurniawan through Tiktok indirectly improved the image of the police in the eyes of the public.